The state and industrialization in Turkey since the nineteenth century - Şevket Pamuk (Journal of Government and Economics)
State directed industrialization in developing countries became a common strategy after World War II. The success of a small number of countries in East Asia added new dimensions to the debates on the role of states in taming domestic and international market forces. However, it soon became evident that states and government-private sector relations in developing countries show a great deal of variation which is reflected in the different degrees of success with state directed industrialization. This paper focuses on a country which has experienced above average rates of industrialization but has not been amongst the most successful cases. It examines the evolution of the larger political order, the state-private sector relations and the related “micro” institutions in four periods. One key finding is that the international environment has not always been conducive to industrialization. Moreover, industrialization outcomes did not depend on a single or a specific set of institutions but on the relations between the political and private sector elites, and more generally, on the political economy.